Staphylococcus aureus resistance to non-β-lactam antibiotics: global genomic epidemiology and machine learning feasibility assessment - Saeid Sadeghi Ghazi Chaki; Maryam Abdulrahman Najim; Lina A. Hassan; Saleh A. S. AlAbdulhadi; Zahraa Abbas Al-Khafaji; M. K. Sharma; Ahmed Shihab Ahmed; Ali Batool Ahmed; Malik Bader Alazzam; Mohammad Sholeh (Molecular Genetics and Genomics, 2026)

Microwave-induced eustress in Datura innoxia: Integrated photosynthetic, oxidative, and cellular responses to a low-dose hormetic elicitor - M. Masroor A. Khan; Tahoora Batool; Azhar Ali; Saif Ali Khan; M. Naeem; Mohammad Mukarram (Biocatalysis and Agricultural Biotechnology, 2026)

Knockdown of circFOXN3 Promotes the Proliferation and Differentiation of Bovine Myoblasts - Xiangyang Guo; Yi Song; Maryam Alenize; Raha Osailan; Yu Li; Fan Xu; Shubin Fu; Afnan O. Deebani; Aaishah M. H. Kaabi; Zahrah R. Alrayes; Uzma Batool; Gongwei Zhang; et al. (Probiotics and Antimicrobial Proteins, 2026)

A review on polymeric and nanocomposite materials for heavy metal removal from water: bibliometric analysis - M. N. Haider; M. Naveed; A. Shah; A. Arjunan; L. S. Jasim; T. B. Tariq; M. A. Zawar; T. Javed; K. Saadallah; M. Batool (International Journal of Energy and Water Resources, 2026)

Challenges in developing effective sensing materials for low-temperature electrochemical N2O detection in freezing soil conditions - SyedaSitwat Batool; Syeda Maria Batool; T. DeSutter; M. Meehan; P.G. Oduor (Journal of Environmental Management, 2026)

Mathematical modeling and simulation of agrowaste packed fixed-bed adsorption columns for methyl green decontamination - M. M. Awan; M. A. Alvi; F. Batool; A. Abbas; M. Adnan; H. Y. Gondal; Y. Gull; U. Younas; Z. Saeed (International Journal of Environmental Science and Technology, 2026)

Carboxymethyl cellulose: Structural modifications and their impact on barrier and mechanical properties for sustainable food packaging - Batool Esmat; Shumaila Bibi; Mohamed Mohamed Soliman; Hamdy Khamees Thabet; Muhammad Ahmad Wattoo; Muhammad Altaf Nazir; Zeinhom M. El-Bahy; Aziz ur Rehman (Journal of Stored Products Research, 2026)

Is grip strength a marker for cognitive function, neurodegeneration, and resilience? - Alexander Ivan B. Posis; Hilary L. Colbeth; Mihika S. Deshpande; Kristen M. George; Batool Rizvi; Rifat B. Alam; Ruijia Chen; Dan M. Mungas; Paola Gilsanz; María M. Corrada; Rachel A. Whitmer (GeroScience, 2025)
Assessing whether grip strength is associated with cognitive decline and brain health could help identify a target to prevent or delay cognitive impairment. Therefore, we tested whether grip strength is associated with brain health as indicated by magnetic resonance imaging and domain specific cognitive decline. We also assessed whether grip strength was a cognitive resilience proxy using moderation tests. This study included cognitive and neuroimaging data from 861 participants in three harmonized cohorts. We fit multivariable linear mixed-effects and linear regression models to test associations between grip strength, neuroimaging markers, and cognition. We also tested moderation by gender and age. Greater grip strength was associated with slower verbal episodic memory decline and greater total gray matter volume. Associations of grip strength with executive function, total hippocampal volume, and white matter hyperintensities were not significant, but in the expected direction. Age moderated associations of grip strength and white matter hyperintensities. Grip strength was a significant proxy for cognitive resilience related to white matter hyperintensity volume and verbal episodic memory decline only. Future research should examine other measures of physical performance that are associated with later-life cognitive and brain health.

Retraction notice to “The construction of novel CuO/SnO2@g-C3N4 photocatalyst for efficient degradation of ciprofloxacin, methylene blue and photoinhibition of bacteria through efficient production of reactive oxygen species” [Environ. Res. Volume 231, Part 1, 15 August 2023, 116086] - Irum Batool; Karma Albalawi; Afaq Ullah Khan; Kamran Tahir; Zia Ul Haq Khan; Magdi E.A. Zaki; Ebraheem Abdu Musad Saleh; Eman A. Alabbad; Talal M. Althagafi; Fahad Abdulaziz (Environmental Research, 2025)

Removal of chromium from electroplating wastewater using chitosan-coconut shell composite: kinetics, thermodynamics and artificial neural networks modeling - F. Batool; T A Kurniawan; B Pasaribu; T D Kusworo; S. Silviana; H S Kusuma; M. I. Khan; S. Haddout; J C C Casila; H. Harianingsih; W O Choo; M A Iqbal (International Journal of Environmental Science and Technology, 2025)

Bimetallic nanoparticles loaded on waste derived carbon quantum dots: A green approach for degradation of azo dye - Saima Ameer; Ehab A. Abdelrahman; Fozia Batool; Asifa Batool; Taslim Akhtar; Abdulrahman G. Alhamzani; Mortaga M. Abou-Krisha (International Biodeterioration & Biodegradation, 2025)

Nature, depositional dynamics, sources, and health risk assessment of indoor microplastics in three cities of Punjab, Pakistan - I. Batool; A. Qadir; J. M. Levermore; F. J. Kelly (International Journal of Environmental Science and Technology, 2025)

Developing an ocean governance regime for China-Pakistan economic corridor: a comparison of the marine environmental legislation and policy framework by utilizing CRILL methodology - Shijun Zhang; Qian Wu; M Jahanzeb Butt; Minerva Batool; Muhammad Murad Zaib Butt (Frontiers in Marine Science, 2025)
Bilateralism in ocean governance is a novel concept that can be developed under the existing International Environmental Law (IEL) and United Nations Convention on the Law of the Sea (UNCLOS). This research paper suggested that bilateralism in ocean governance is one of the Agenda of Sustainable Development Goal 14 (SDG 14). This research paper utilized the methodology of a Comprehensive Review of Law and Relevant Literature (CRILL methodology) and developed a theoretical and legal framework for bilateral ocean governance with the elements of capacity building, adaptation, precautionary approach and participation. Under the given elements of CRILL methodology, this paper analyzed and compared the ocean governance mechanisms of China and Pakistan and proposed that under the China-Pakistan Economic Corridor (CPEC) of the Belt and Road Initiative (BRI), these two States can develop a bilateral framework of ocean governance for the protection of the marine environment, preservation of fisheries and mitigation of ocean acidification and sea level rise. The results of the CRILL methodology are presented in the form of a proposal that institutional coordination is essential for the effectiveness of bilateral ocean governance cooperation, which is China’s regional agenda of BRI. Through such development, the two States, China and Pakistan, can share the mutual economic benefits of ocean development and can have a strong voice in the global ocean agenda.

Green Synthesis of Zinc Oxide Nanoparticles, Characterization and Its Applications in Inducing Disease Resistance Against Spot Blotch Disease in Wheat by Enhancing Its Physiological and Biochemical Parameters - Asif Kamal; Jinguang Yang; Momal Batool; Ulfat Ara; Waseem Ahmed Khattak; Driss Touhami; Reem M. Aljowaie; Mohamed S. Elshikh (Journal of Crop Health, 2025)

Foliar epidermal micromorphology: a contribution to the taxonomy of family Oleaceae - Tajalla Batool; Muhammad Zafar; Mohamed S. Elshikh; Abd El-Zaher M. A. Mustafa; Mushtaq Ahmad; Trobjon Makhkamov; Sokhib Islamov; Dilnoza Sotiboldiyeva; Akramjon Yuldashev; Mozaniel Santana De Oliveira; Salman Majeed; Inomjon Bakhramov; et al. (Genetic Resources and Crop Evolution, 2025)

Babesia bigemina and Theileria annulata infections in cattle: molecular detection, phylogenetic analysis, and assessment of risk factors - Majid Khan; Mehran Khan; Momin Khan; Sidra Batool; Tetsuya Tanaka; Abdulaziz Aloufi; Mashal M. Almutairi; Abid Ali (Tropical Animal Health and Production, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Novel green sorbent Aerva Javanica for dyes remediation from aqueous media and future prediction through QSPR modeling - H. Y. Gondal; F. Batool; S. Iqbal; J. Akbar; S. Noreen; M. Mustaqeem; M. F. ur Rehman; M. Imtiaz; R. Qadir (International Journal of Environmental Science and Technology, 2024)

New U-Pb zircon geochronological data for Takestan magmatic rocks (Western Alborz) and their significance for the interpretation of Paleogene magmatism in Iran - Ali A. Sepahi; Batool Nemati; Abbas Asiabanha; David R. Lentz; Chris R. M. McFarlane (International Geology Review, 2024)

Genetic variability of buckwheat (Fagopyrum spp.) genotypes for nutritional and nutraceutical traits - Madhiya Manzoor; Ammarah Hami; Mohammad Maqbool Pakhtoon; Aneesa Batool; Aaqif Zaffar; Jebi Sudan; Gowhar Ali; Mohammad Anwar Khan; Parvaze Ahmad Sofi; Reetika Mahajan; Bilal Ahmad Bhat; Roohi Mushtaq; et al. (The Nucleus, 2024)

Customized plant microbiome engineering for food security - Maria Batool; Lilia C. Carvalhais; Brendan Fu; Peer M. Schenk (Trends in Plant Science, 2024)

Comparison between carbon nanotubes and molybdenum trioxide nanoparticles embedded in polymeric membrane for environmental remediation - A. Abbass; S. Hassan; Z. Imran; S. S Batool; M. Ahmed; A. I Ahmad; D. Mazhar; S. Zaman (International Journal of Environmental Science and Technology, 2024)

RETRACTED: The construction of novel CuO/SnO2@g-C3N4 photocatalyst for efficient degradation of ciprofloxacin, methylene blue and photoinhibition of bacteria through efficient production of reactive oxygen species - Irum Batool; Karma Albalawi; Afaq Ullah Khan; Kamran Tahir; Zia Ul Haq Khan; Magdi E.A. Zaki; Ebraheem Abdu Musad Saleh; Eman A. Alabbad; Talal M. Althagafi; Fahad Abdulaziz (Environmental Research, 2023)

Erratum to ‘Role of endophytic bacteria in salinity stress amelioration by physiological and molecular mechanisms of defense: A comprehensive review’ South African Journal of Botany, Volume 151, December 2022, Pages 33-46 - Baber Ali; Aqsa Hafeez; Muhammad Ammar Javed; Muhammad Siddique Afridi; Hina Ali Abbasi; Ayesha Qayyum; Tayyaba Batool; Abid Ullah; Romina Alina Marc; Soad K. Al Jaouni; Dalal Hussien M. Alkhalifah; Samy Selim (South African Journal of Botany, 2023)

Insect-facilitated propagation of mycotoxic fungi in grain storages: association of Sitotroga cerealella Olivier with Aspergillus flavus link - A. A. Khan; U. Umar; S. Ejaz; H. Riaz; M. Batool; T. Chen; F. Ahmad; Q. Saeed (International Journal of Environmental Science and Technology, 2023)

Assessment of heavy metal contamination and its sources in urban soils of district Hyderabad, Pakistan using GIS and multivariate analysis - R. K. Bux; S. I. Haider; M. Batool; A. R. Solangi; Z. Shah; H. Karimi-Maleh; F. Sen (International Journal of Environmental Science and Technology, 2022)

Copper chromite/graphene oxide nanocomposite for capacitive energy storage and electrochemical applications - R. Shafique; M. Rani; A. Mahmood; S. Khan; N. K. Janjua; M. Sattar; K. Batool; T. Yaqoob (International Journal of Environmental Science and Technology, 2022)

Genetic Association of Butyrylcholinesterase with Major Depressive Disorder - Sliha Awan; Aisha N. Hashmi; Rizwan Taj; Sadaf Munir; Rabia Habib; Sajida Batool; Maleeha Azam; Raheel Qamar; Syed M. Nurulain (Biochemical Genetics, 2022)

Integrated usage of synthetic and bio-fertilizers: an environment friendly approach to improve the productivity of sorghum - S. Akhtar; S. Bashir; S. Khan; J. Iqbal; A. B. Gulshan; S. Irshad; S. Batool; N. Ahmad; M. S. Rizwan (Cereal Research Communications, 2020)

Screening of maize hybrids against salt stress under hydroponic culture - M. M. Maqbool; A. Wahid; A. Ali; S. Khan; S. Irshad; S. Batool (Cereal Research Communications, 2020)

Butyrylcholinesterase in Substance Abuse: An Overview - S. M. Nurulain; A. Adem; S. Munir; R. Habib; S. Awan; F. Anwar; S. Batool (Neurophysiology, 2020)

Association of vascular endothelial growth factor (VEGF) Gene polymorphisms and expression with the risk of endometriosis: a case–control study - Batool Hossein Rashidi; Negar Sarhangi; Soheila Aminimoghaddam; Fedyeh Haghollahi; Tahereh Naji; Mahsa M. Amoli; Maryam Shahrabi-Farahani (Molecular Biology Reports, 2019)

Author Correction: Enhanced Approaches to the Identification, Evaluation, and Control of Impurities - Matt E. Popkin; Phil J. Borman; Batool Ahmed Omer; Adam Looker; Jeffrey M. Kallemeyn (Journal of Pharmaceutical Innovation, 2019)

Enhanced Approaches to the Identification, Evaluation, and Control of Impurities - Matt E. Popkin; Phil J. Borman; Batool Ahmed Omer; Adam Looker; Jeffrey M. Kallemeyn (Journal of Pharmaceutical Innovation, 2019)

Biochemical Analysis and Association of Butyrylcholinesterase SNPs rs3495 and rs1803274 with Substance Abuse Disorder - Sadaf Munir; Rabia Habib; Sliha Awan; Nazia Bibi; Arooj Tanveer; Sajida Batool; Syed M. Nurulain (Journal of Molecular Neuroscience, 2019)

The Delivery of Flexibility from the Application of QbD to API Development - Matt E. Popkin; Phil J. Borman; Batool Ahmed Omer; Kevin D. Seibert; Sushil Srivastava; John V. Lepore; Lindsay Hobson; John Donaubauer; Timothy Curran; Nathan Ide; Steven Tymonko; Adam Looker; et al. (Journal of Pharmaceutical Innovation, 2018)

Comparison of different phases of bismuth silicate nanofibers for photodegradation of organic dyes - S. S. Batool; S. Hassan; Z. Imran; K. Rasool; M. Ahmad; M. A. Rafiq (International Journal of Environmental Science and Technology, 2016)

Microbial transformation of oleanolic acid by Fusarium lini and α -glucosidase inhibitory activity of its transformed products - M. Iqbal Choudhary; Iffat Batool; Shamsun Nahar Khan; Nighat Sultana; S. Adnan Ali Shah; Atta-Ur-Rahman (Natural Product Research, 2008)

Preliminary assessment of plant community structure and arbuscular mycorrhizas in rangeland habitats of Cholistan desert, Pakistan - M. S. Chaudhry; Z. Batool; A. G. Khan (Mycorrhiza, 2005)